2007
DOI: 10.1016/j.jns.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial toxins and Multiple Sclerosis

Abstract: The primary pathogenetic mechanism responsible for the distinctive demyelinating lesions in the Central Nervous System (CNS) in Multiple Sclerosis (MS), first described in remarkable detail by Charcot more than 170 years ago, remains one of the most baffling conundrums in medicine. A possible role for bacterial cell molecules and transportable proteins in the pathogenesis of MS is reviewed. The ability of bacterial toxins to distort immunity and to cause distinctive toxic damage in the nervous system is discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…As anosmia can similarly occur early in MS, pathological involvement of the olfactory bulb/tract and its relationship to adjacent cortical demyelination may not only explain this symptom but also may spin a different light onto observations which link chronic sinusitis to MS susceptibility, relapse risk and its demography (figure 5). 64 65 In ADEM where olfactory bulb/tract demyelination is highly inflammatory and symptom onset occurs within days, disease is typically preceded by contraction of an upper respiratory tract infection (URTI) 68. Might the olfactory system play a role in permitting a nasopharyngeal agent into the CNS where it initiates a process of acute or chronic neuroinflammation?…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 99%
“…As anosmia can similarly occur early in MS, pathological involvement of the olfactory bulb/tract and its relationship to adjacent cortical demyelination may not only explain this symptom but also may spin a different light onto observations which link chronic sinusitis to MS susceptibility, relapse risk and its demography (figure 5). 64 65 In ADEM where olfactory bulb/tract demyelination is highly inflammatory and symptom onset occurs within days, disease is typically preceded by contraction of an upper respiratory tract infection (URTI) 68. Might the olfactory system play a role in permitting a nasopharyngeal agent into the CNS where it initiates a process of acute or chronic neuroinflammation?…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 99%
“…Recent studies have demonstrated that the liquor is mostly drained by the lymphatic system, flowing from the perineural and perivascular sheaths to the lymphatic vessels; when it is in the lymphatic system, the liquor flows to the cribriform plate of the ethmoid bone, and then to the epithelium and the nasal mucosa (Figure 6). 103,104…”
Section: Clinical Scenarios: Facts and Hypothesesmentioning
confidence: 99%
“…An imbalance in the quantity of liquor can alter the immunological environment, whether cerebral or systemic, as it transports many substances (ie, electrolytes, catabolites, hormones and neuropeptides) 100,104,107. Altered homeostasis of the nasal mucosa and of the olfactory nerve can develop disorders in the superior respiratory tract, which can convey germs to the cerebral area, through the lymphatic pathways departing from the brain 104…”
Section: Clinical Scenarios: Facts and Hypothesesmentioning
confidence: 99%
“…Highly significant clinical, epidemiological and pathogenetic similarities between multiple sclerosis and nasopharyngeal sinusitis has led to the hypothesis that MS is caused by the leakage of bacterial toxins generated by the flora of the paranasal sinuses into the extracellular fluid compartments of the CNS (Gay, 2007). The inflammation observed in the trans-cisternal trigeminal nerve of MS patients may be the result of ascending lymphatic drainage Contents lists available at SciVerse ScienceDirect journal homepage: www.elsevier.com/locate/msard from the nasopharynx, as described by Orr and Rose (1914).…”
mentioning
confidence: 99%